Exposure to low Earth orbit of an extreme-tolerant cyanobacterium as a contribution to lunar astrobiology activities. Issue 1 (18th February 2020) - Billi, Daniela; Mosca, Claudia; Fagliarone, Claudia; Napoli, Alessandro; Verseux, Cyprien; Baqué, Mickael; de Vera, Jean-Pierre
Abstract: By investigating the survival and the biomarker detectability of a rock-inhabiting cyanobacterium, Chroococcidiopsis sp. CCMEE 029, the BIOMEX space experiment might contribute to a future exploitation of the Moon as a test-bed for key astrobiology tasks such as the testing of life-detection technologies and the study of life in space. Post-flight analyses demonstrated that the mixing of dried cells with sandstone and a lunar regolith simulant provided protection against space UV radiation. During the space exposure, dried cells not mixed with minerals were killed by 2.05 × 10 2 kJ m −2 of UV radiation, while cells mixed with sandstone or lunar regolith survived 1.59 × 10 2 and 1.79 × 10 2 kJ m −2, respectively. No differences in survival occurred among cells mixed and not mixed with minerals and exposed to space conditions in the dark; this finding suggests that space vacuum and 0.5 Gy of ionizing radiation did not impair the cells' presence in space. The genomic DNA of dead cells was severely damaged but still detectable with PCR amplification of a short target, thus suggesting that short sequences should be targeted in a PCR-based approach when searching for traces of life. The enhanced stability of genomic DNA of dried cells mixed with minerals and exposed to space indicates that DNA might still be detectable after prolonged periods, possibly up to millions of years in microbes shielded by minerals. Overall, the BIOMEX results contribute to future experiments regarding the exposure of cells and their biomarkers to deep space conditions in order to further test the lithopanspermia hypothesis, the biomarker stability and the microbial endurance, with implications for planetary protection and to determine if the Moon has been contaminated during past human missions.